Towards net-zero wastewater treatment: Integrating wind, solar, and hydrogen storage in arid regions - Kalantari, Mobina; Yousefi, Hossein; Hajinezhad, Ahmad; Abdoos, Mahmood (Edelweiss Applied Science and Technology, 2025)
The increasing energy demand and environmental pressures faced by wastewater treatment plants (WWTPs) necessitate the development of sustainable, cost-effective, and flexible energy solutions, especially in arid regions. Addressing a critical research gap in the literature, namely, the limited exploration of long-term hydrogen-based energy storage in real-world wastewater applications, this study proposes an innovative hybrid energy management framework integrating solar, wind, and hydrogen technologies for a WWTP in Lusail, Qatar. Unlike previous studies that relied on solar–wind systems with batteries or theoretical models, this work uniquely employs real operational data and detailed HOMER simulations to validate the techno-economic and environmental benefits of hydrogen integration. Simulation results show that the proposed solar–wind–hydrogen configuration achieves a significant annual CO2 reduction of 1,534,388 kg, outperforming battery-based systems without storage. The hydrogen-powered system ensures superior long-term energy flexibility, strong economic viability, and notable environmental advantages, offering a scalable model for future sustainable wastewater treatment infrastructure in harsh climates. Overall, the findings provide a practical framework for optimizing energy consumption and advancing energy sustainability in industrial wastewater treatment plants operating in arid and high-demand regions.